2014
DOI: 10.1016/j.ecolmodel.2014.09.004
|View full text |Cite
|
Sign up to set email alerts
|

First 20 years of DNDC (DeNitrification DeComposition): Model evolution

Abstract: A B S T R A C TMathematical models, such as the DNDC (DeNitrification DeComposition) model, are powerful tools that are increasingly being used to examine the potential impacts of management and climate change in agriculture. DNDC can simulate the processes responsible for production, consumption and transport of nitrous oxide (N 2 O). During the last 20 years DNDC has been modified and adapted by various research groups around the world to suit specific purposes and circumstances. In this paper we review the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
104
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 227 publications
(106 citation statements)
references
References 58 publications
0
104
0
2
Order By: Relevance
“…Considering that the field-scale study showed similar results as the smallscale laboratory incubation, it would appear that the DNDC model does not include specific soil processes that limit microbial activity after fertilizer addition. Predictions related to N fertilization have been yet reported to be a weakness in DNDC (Gilhespy et al 2014). To improve the model, more experimental research is required to fully understand the interactions between fertilizer additions and microbial activity.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that the field-scale study showed similar results as the smallscale laboratory incubation, it would appear that the DNDC model does not include specific soil processes that limit microbial activity after fertilizer addition. Predictions related to N fertilization have been yet reported to be a weakness in DNDC (Gilhespy et al 2014). To improve the model, more experimental research is required to fully understand the interactions between fertilizer additions and microbial activity.…”
Section: Discussionmentioning
confidence: 99%
“…Greenhouse gas emissions associated with agriculture (including livestock systems and biogeochemical processes) will be quantifi ed with the use of existing models (eg, the DAYCENT or DeNitrifi cation-DeComposition [DNDC] models). [69][70][71] An understanding is needed of the potential for multiple environmental factors to aff ect food systems, and the nuances within and between countries and cultures. Further work will be required to refi ne indicators for this area, and the scientifi c community is invited to suggest potential metrics and data sources.…”
Section: Productionmentioning
confidence: 99%
“…According to the literature, the validation of the model could be done based on: (i) crop yield and biomass, (ii) soil data, and (iii) gas emissions [35]. The calibration of the DNDC model to Polish terms performed on the foundation coefficients developed for crops at regional scale in the EU-15 [44].…”
Section: Denitrification Decompositionmentioning
confidence: 99%
“…The DNDC model was used by the European Union (EU) to set sustainability criteria for biofuels with the legislation of the RED [4]. Detailed model development is presented by Gilhespy et al [35], and Zhang and Niu [27]. The DNDC model was validated globally in over 100 studies, which has demonstrated accurate predictions of crop yields, climate, nitrogen losses, carbon sequestration and GHG emissions from agro-ecosystems [27,[36][37].…”
mentioning
confidence: 99%